Fairness in the family: implications for parent-adult child interactions - John Ermisch (University of Essex, Institute for Social and Economic Research (ISER), 2006)
This paper advances the hypothesis that transfers of contact/in-kind help and money between parents and an adult child reflect concerns for fairness and reciprocity, and may be interpreted as a gift exchange. It is inspired by recent evidence from experiments that suggests that even strangers behave in accordance with concerns for fairness and reciprocity. The implications of this hypothesis for the relationship between parents resources and frequency of contact/in-kind are contrasted with those of efficient exchange and family constitution models of intergenerational transfers. Empirical evidence from the British Household Panel Study provides stronger support for the gift exchange model than the efficient exchange or binding constitution models.
Keywords: 330